One-pot synthesis of 3D Cu2S–MoS2 nanocomposites by an ionic liquid-assisted strategy with high photocatalytic activity. (28th November 2018) - Chen, Ya; Su, Penghe; Liu, Xiaotong; Liu, Hongchi; Zhu, Baolin; Zhang, Shoumin; Huang, Weiping
Abstract : Cu2 S–MoS2 nanocomposites are synthesised by a one-step hydrothermal method and show better catalytic activity than Cu2 S and MoS2 monomers. Abstract : Novel 3D Cu2 S–MoS2 ( x  :  y ) nanocomposites with different proportions of Cu2 S ( x ) and MoS2 ( y ) are synthesized successfully by a one-step hydrothermal method with the assistance of the ionic liquid [BMIM]SCN. The characterization results show that the nanocomposites are self-assembled from nanosheets of Cu2 S and MoS2, they display nanoflower morphology and a typical mesoporous structure. The fabrication mechanism of the nanocomposites is investigated using time-dependent experiments, which indicate the key role of the ionic liquid (IL) in the synthesis process. Furthermore, TAA is used as a sulfur source instead of the IL to form a Cu2 S–MoS2 nanocomposite, with the aim of further investigating the effects of the IL on the morphology of the composite. Photodegradation of MB under visible light irradiation experiments were used as probe reactions to evaluate the photocatalytic performance of the as-prepared samples. All the nanocomposites show better catalytic activity than Cu2 S and MoS2 monomers. Among the different Cu2 S–MoS2 ( x  :  y ) nanocomposites, the Cu2 S–MoS2 (1 : 1) composite exhibits the most excellent photocatalytic performance and cycling stability.